2022
DOI: 10.1088/2051-672x/ac9c20
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on simultaneous machining of EDM and ECM with different electrode materials

Abstract: In order to improve the machining efficiency and the surface quality of EDM/ECM, adding a small amount of sodium nitrate into deionized water as the working medium, a novel simultaneous machining approach of EDM and ECM (SEDCM) was developed. In this work, a comparative study was conducted on the SEDCM performance of TC4 alloy using different electrode materials viz. brass, copper and copper-tungsten alloy. In addition, the effects of process parameters, such as peak current, pulse on time and gap voltage on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…As discussed earlier, 4 μs was the optimal Toff, as all the electrode used for the investigation proffers maximum MRR. In case of Ton, MRR increases linearly when Cu was used as the electrode, it declines after 8 μs in case of A1 composite tool [31]. The optimal current for copper tool was 9 A and in case of composite tool it increased to 12 A, as the MRR of 49.97 mm 3 min −1 and 46.37 mm 3 min −1 was recorded for the above mentioned parametric setting respectively [32].…”
Section: Influence Of Various Process Parameters On the Mrr Of Incone...mentioning
confidence: 85%
“…As discussed earlier, 4 μs was the optimal Toff, as all the electrode used for the investigation proffers maximum MRR. In case of Ton, MRR increases linearly when Cu was used as the electrode, it declines after 8 μs in case of A1 composite tool [31]. The optimal current for copper tool was 9 A and in case of composite tool it increased to 12 A, as the MRR of 49.97 mm 3 min −1 and 46.37 mm 3 min −1 was recorded for the above mentioned parametric setting respectively [32].…”
Section: Influence Of Various Process Parameters On the Mrr Of Incone...mentioning
confidence: 85%
“…This is because the ion dissolution mainly occurs at the surface after EDM, which increases the entrance diameter. Meng et al [15] used SEDCM to study the effect of peak current and pulse duration on the machined surface and concluded the same.…”
Section: Peak Current and Pulse Width Durationmentioning
confidence: 89%
“…As a result, thermal damage and crater marks may remain on the machined surface. Recently, Meng et al (2022) 23 and Ahmed et al ( 2022) 24 investigated simultaneous machining with low-concentration electrolyte solutions. However, these studies did not provide specific insights into overcutting, leaving a notable gap in the research.…”
mentioning
confidence: 99%
“…It is important to note that the application of higher voltages in conjunction with electrolyte solutions to enhance polishing may lead to potential overcutting, especially given the reported Ra values within the range of 3 to 5 μm. 23 The above-cited literature highlights that the simultaneous approach entails the application of rather high voltage to generate electrical discharges, leading to overcutting and large hole sizes or low-conductivity solutions that reduce overcutting but compromise material removal and polishing. To address this, the sequential execution of EDM and ECM processes on a single machining facility proves to be a more viable option.…”
mentioning
confidence: 99%